Cytotoxic activity of different fractions of Tinospora Crispa stems extracts - Sasikala, Mahalingam (2012)
"Patawali" (Malay) refers to Tinospora crispa (Menispermaceae) which has been claimed to have many traditional uses. The root, stem and leaves of this plant have been used for many medicinal purposes such as fever, diabetes and rheumatism. Tinospora crispa contains variety of phytochemicals. In this study, the powdered Tinospora crispa stems were extracted using different solvents and pH to obtain five fractions (Fraction 1, 2, 3, 4 and 5) with varying polarity. These fractions were then screened for cytoxicity test using brine shrimp lethality assay. For each fraction, 3 concentrations were prepared (10, 100 and 1000 .tg/mL) and the assay was conducted in triplicates. The result obtained showed only Fraction 3 and 4 were toxic with LC 50 value of 41.59 jig/mL and 118.58 ig/mL respectively whereas Fraction 1, 2 and 5 did not exhibited any LC 50 value for the range of concentrations prepared. Brine shrimp lethality assay results from this study may be used as preliminary indication as anticancer agent of the likely presence of toxic compounds in those particular fractions. Other cytotoxicity tests and specific bioassays may be done on the isolated bioactive compounds later.